Mrs. Morris and the wolfman - Wilton, Traci (Wilton, Traci. Salem B&B mystery., 2023)
Charlene Morris, with a little help from the handsome ghost who haunts her B & B, sets out to discover who upstaged the grand reopening of one of Salem's classic theaters with murder before the credits roll.